Life Cycle and Development of Diptera - Sarwar, Muhammad (IntechOpen, 2020)
Diptera, or true flies, are of considerable economic importance, as these flies have a valuable role as scavengers, parasitoids and predators of other insects, pollinators, food for predators, bio-indicators of water quality, and tools for scientific research. In nine chapters, this book examines various aspects of flies of the order Diptera as well as some types of mosquitos and midges. Topics covered include taxonomy, phylogeny, life cycle, feeding habits, population control strategies, and more. A unique chapter on forensic entomology is particularly interesting. Beautifully illustrated and expertly researched, this volume will appeal to entomologists, biologists, and naturalists.